A tumor-sensitive biological metal–organic complex for drug delivery and cancer therapy. Issue 32 (3rd July 2020) - Jiang, Zelei; Wang, Tong; Yuan, Shuai; Wang, Mengfan; Qi, Wei; Su, Rongxin; He, Zhimin
Abstract : Tumor-sensitive bioMOC-Zn(Cys) was developed using an endogenous Zn 2+ ion and l -cystine for the delivery of anti-cancer drug DOX. In vivo application of DOX@bioMOC-Zn(Cys) shows the increased inhibition of tumor growth and prevented side effects. Abstract : Metal–organic complexes (MOCs) or metal–organic frameworks (MOFs) have attracted increasing interest for constructing nanoscale drug delivery systems for cancer therapy. However, conventional MOC/MOF materials usually contain toxic metals or low-biocompatible organic ligands. Also, current approaches for creating tumor-sensitive nanocarriers are always based on the instability of coordination bonds under acidic conditions, or through post-synthetic modification with sensitive molecules. As a matter of fact, it is more facile to fabricate tumor-sensitive MOCs/MOFs based on the stimuli-responsiveness of organic ligands. In this study, a novel tumor-sensitive biological MOC (bioMOC-Zn(Cys)) was created through the assembly of endogenous Zn 2+ ions and the small biological molecule (l -cystine, Cys). The disulfide bond in l -cystine is cleavable by the overexpressed GSH in tumor cells, thus achieving rapid release of drugs from nanocarriers. By encapsulating doxorubicin (DOX) in bioMOC-Zn(Cys), DOX@bioMOC-Zn(Cys) displayed higher cellular uptake and cytotoxicity in cancer cells than free DOX. In vivo investigations indicated that DOX@bioMOC-Zn(Cys) largely inhibited tumor growth and reduced side effects. Remarkably, since both metal ions and organic ligands were obtained from biological sources, bioMOC-Zn(Cys) exhibited superior biocompatibility. This study presents a new method for fabricating MOC-based nanodrugs with high tumor-sensitivity and low toxicity.